Multi-Step Combined Upfront Surgery for Locally Advanced Paravertebral Sarcoma: A Case Report - Cariboni, Umberto; Gennaro, Nicolò; Costa, Francesco; Renne, Salvatore Lorenzo; Novellis, Pierluigi; Marrari, Andrea; Bertuzzi, Alexia Francesca; Civilini, Efrem (Frontiers in Surgery, 2021)
Background Paravertebral localization of primary undifferentiated pleomorphic sarcoma (UPS) with bone and vascular involvement is infrequent and challenging. Multi-step surgical procedure has been described as a feasible and effective option to achieve sustained local tumour control. Methods We report on a 62-year old man with paravertebral UPS infiltrating the aortic wall and the 9th thoracic vertebra who underwent a multi-step surgical procedure aimed at achieving oncologic radicality through a coordinated effort between thoracic, vascular and spinal surgeons. After balancing the risks and benefits of perioperative therapies, upfront surgery was performed including aortic resection with bypass grafting followed by a triple en bloc vertebrectomy with tumour excision. Mid-term follow-up (22 months) is then provided. Results The combined procedure achieved oncological radicality and no local recurrence in the mid-term. No major complications occurred. Conclusions Multi-step and multi-specialty surgery is a feasible and effective strategy to treat primary UPS in unfavourable localisation. A strategic cooperation between surgeons and a multidisciplinary tumour board is required to define an optimal, personalised treatment strategy in sarcoma patients.